The Antarctic : A Very Short Introduction - Dodds, Klaus (Oxford Oxford University Press, 2012)
Antarctica attracts great interest from political leaders, journalists, and public audiences around the world. In this Very Short Introduction, Klaus Dodds presents a modern account of Antarctica, looking closely at contemporary developments in commerce, science, sovreignty, and governance.
Include Illustrations and Index
Keywords: Antarctica